Features of Formation of the Nanoparticles of Alloys in Metal-carbon Nanocomposites FeCo / C and NiCo / C on Based Polyacrylonitrile - L.V. Kozhitov; D.G. Muratov; V.G. Kostishin; A.G. Savchenko; I.V. Schetinin; A.V. Popkova; E.V. Yakushko; L.M. Chervjakov (Журнал нано- та електронної фізики)
By the method of IR-heating the precursor on base of polyacrylonitrile, compounds of iron, cobalt and nickel metal-carbon nanocomposites were obtained, representing an ensemble of nanoparticles of intermetallic FeCo (NiCo), dispersed in nanocrystalline carbon matrix. XRD analysis revealed that the carbon structure of the PAN-based matrix changed from amorphous to nanocrystalline at the processing temperatures in the range 200-700 °C. Thus there is a reduction of metals from compounds released by degradation of the polymer with hydrogen. FeCo alloy nanoparticles formed at synthesis temperatures T > 500 °C, in the case of nanocomposites NiCo / C alloy nanoparticle formation is possible at T ≥ 270 °C, which is associated with a lower temperature compared to the recovery of nickel from iron. According to the results of TGA and DSC found that metals are capable of initiating the chemical transformation in the PAN, resulting in reduction start temperature degradation. According to the results of DSC revealed that the formation of nanoparticles is accompanied by release of heat due to exothermic processes occurring in the nanocomposites.